2019
DOI: 10.1021/acs.chemmater.9b01299
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of a Magnesium Phosphate Solid Electrolyte

Abstract: Atomic layer deposition (ALD) was used to fabricate magnesium phosphate thin films as a magnesium-ion conducting solid electrolyte. The deposition was carried out at lower deposition temperatures, ranging from 125 to 300 °C. The film exhibits an amorphous nature and excellent step coverage, even in narrow trenches with a higher aspect ratio. The growth rate and the ionic conductivity were found to increase with a decrease of the deposition temperature. This can be explained by increased disordering of the phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 52 publications
(89 reference statements)
1
36
0
Order By: Relevance
“…To improve both the stability and the photocurrent, it is therefore essential to increase the quality of the surface modification materials. In future, atomic layer deposition (ALD) could represent a suitable means of fabricating pinhole‐free conformal coatings of stable oxides. Poisoning of the Pt catalyst in the Pt/CdS/CdTe(CdCl 2 )/Cu/Au/FTO photocathode could also have caused the deactivation of the tandem PEC cell .…”
Section: Resultsmentioning
confidence: 99%
“…To improve both the stability and the photocurrent, it is therefore essential to increase the quality of the surface modification materials. In future, atomic layer deposition (ALD) could represent a suitable means of fabricating pinhole‐free conformal coatings of stable oxides. Poisoning of the Pt catalyst in the Pt/CdS/CdTe(CdCl 2 )/Cu/Au/FTO photocathode could also have caused the deactivation of the tandem PEC cell .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the progresses discussed above for LIBs, lithium metal batteries, and 3D solid-state microbatteries, there have some new trends emerging for other beyond LIB systems, including sodium-based [20], zinc-based [113], potassiumbased [156], aluminum-based [114], and magnesium-based batteries [157]. Meng has made an updated overview of ALD for SIBs [20].…”
Section: Reviewmentioning
confidence: 99%
“…Atomic layer deposition techniques are able to finely control the thickness of the materials with conformal deposition, as well as the surface chemistry which can enable good interface between the anode and the electrolyte. Recently in 2019, Su et al used ALD to deposit magnesium phosphate thin films on platinum substrate to measure its electrochemical properties (Su et al, 2019). They found that this magnesium phosphate film had an ionic conductivity of 1.6 × 10 -7 S cm −1 at 500°C with an activation energy of 1.37 eV.…”
Section: Progress To Realize Hydrated Vanadium Oxide For Mg Battery Focus On Anode Protection and Solid Electrolytesmentioning
confidence: 99%